Development of Musculoskeletal Problems Caused by Poor Ergonomics in Dentists. Systematic Review - Adriana María García Novillo; Gilson Steven Sánchez Maldonado (Medisur)
Musculoskeletal pathologies are the most common and costly occupational injuries associated with the musculoskeletal system, which generate physical and functional alterations in the joints and other tissues. There is a high prevalence in the dental profession. The objective of the research was to obtain an update of the main considerations on the relationship between poor ergonomics and musculoskeletal pathologies in dental professionals. To achieve the objective, a qualitative approach was used, supported by a systematic, descriptive review and a documentary design that favored the collection of information contained in scientific articles from online databases, through the use of describers of sciences of health, as well as inclusion and exclusion criteria to facilitate the search. 186 scientific articles were collected, 15 were selected as valid after a discarding process. The conclusion was reached of the existence of a relationship between poor ergonomics and the development of musculoskeletal pathologies in dental students and professionals. The main risk factor was found to be maintaining inadequate postures for a long time while exercising one's profession.